Study of the Quantitative Standard of Traditional Chinese Medicine Symptom Classification of Incomplete Spinal Cord Injury - Jun LENG; Li LI; Wanbin LI; Xia ZHOU; Chuanying WANG; Shuzhen XING (康复学报)
Objective:To establish the quantitative standard of Traditional Chinese Medicine (TCM) symptom classification of incomplete spinal cord injury.Methods:The ancient and modern literatures were searched by adopting artificial retrieval, computer retrieval and network retrieval method, with the key words of "atrophy disease" or "spinal cord injury". Syndrome factors of 20 were extracted, including 4 main symptoms, 16 secondary symptoms and 4 radiographic grade. Through the way of a combination of Delphi expert questionnaire and discussion, the quantitative criteria of each symptom was established, weight estimation for the evaluation index in quantitative criteria of the qualitative syndrome severity levels was conducted, and a preliminary qualitative syndrome severity evaluation standard was constructed.Results:Through the above procedures, the quantitative standard of TCM symptom classification of incomplete spinal cord injury was preliminarily constructed.Conclusion:The establishment of the quantitative criteria for the classification of TCM symptoms of incomplete spinal cord injury can preliminarily provide some reference for judging the severity, developing trend and clinical effect of the patients with incomplete spinal cord injury.